Windows Phone 7 recipes a problem-solution approach - Ferracchiati, Fabio Claudio (Apress, 2011)
Developers are racing to discover how to develop for Windows Phone 7?and there is no quicker resource to help you get up to speed than Windows Phone 7 Recipes. This book covers all aspects of development, configuration, testing, and distribution, with detailed code samples and rapid walkthroughs to support you every step of the way. You'll find recipes that unlock advanced user interface development, data storage and retrieval, integration with cloud services, adding media and location-based services, and working with Silverlight and Expression Blend. Learn to use sensors such as the camera, GPS, and accelerometer to build cutting-edge applications. Manage the new way to interact with applications using the gestures library both from the XNA Framework library and the Silverlight Windows Phone Toolkit library.